Autoserum skin tests in allergic patients, and in autistic patients and their mothers - de Almeida Cardoso, Roberto Ronald (Revista Cubana de Pediatría, 2017)
Introduction: allergies are frequently found among patients with autism and autism shows an increased frequency among the allergic patients. Objective: to demonstrate that allergies and autism share some similar immunological patterns. Methods: the autoserum skin test (ASST) was used to demonstrate the presence of anti-IgE and/or anti-IgE receptor antibodies (FcεRIα). Results: the ASST demonstrated similar frequency, positives/positives and negatives/negatives, considering allergic and autistic patients. These similarities didn't exist when comparing with the control group. A positive correlation had been found with the results of autistic patients and their mothers. Conclusions: autistic and allergic patients share some immunological similarities. Both differ from normal controls. It is not uncommon autistics with allergic symptoms and allergic patients with autism. If the immunological findings represent a clinical bridge between both processes, it is under discussion. Also it was demonstrated a possible genetic correlation between the patients with autism and their mothers.